Análise do comportamento visual e da tomada de decisão no voleibol - Henrique de Oliveira Castro (2015)
In sports the visual system contributes to the individual informations of the environment, which relate to each other and converge for decision-making (DM). This project has the intention to (1) verify the visual behavior using the eye tracking (via Eye Tracking fixed); (2) verify the quality of decision-making (DM); and (3) verify the amount of options generated in moments with and without visual occlusion in clips of real game of volleyball athletes and non-athletes. The sample was composed of 48 male volunteers divided into athletes (n=25; mean age of 16.9±1 years) and non-athletes (n=23; mean age of 17.6±1.7 years). It was used the Eye Tracking SMI RED500® to analyze the visual behavior (number and duration of the visual fixation) during the Tactical Declarative Knowledge Test in the General Volleyball - TDKT:GVb. It was used the verbal report of the participants to evaluate the quality of DM and the amount of options generated. It was used the independent t test to compare the two groups in the analyzes of the number of visual fixation for three variables with normal distribution (End Attacking-AE, Blocking-BL and Lifting-LE). For the significant deviation to normality (Central Attacking-AC) we applied to the Mann-Whitney U test. For the duration of visual fixations we opted for the Mann-Whitney U test for comparison between groups. To analyze the quality of DM, we used the chi-square test of proportions. To analyze the number of options generated in moments with and without visual occlusion, we performed the ANOVA two-way for the group (athletes and non-athletes) and moment (with and without occlusion) factors. For the variables which we detect interaction between the principal facts, we performed the deployment analyze. For the duration of visual fixations, we observed a significantly difference for the AC situation, with a faster fixation realized by the athletes. For the quality of DM, significantily differences are revealed on the situations of AE and AC, when athletes and non-athletes are compared, resulting in a higher frequency of correct answers of athletes in relation of non-athletes. For the amount of options generated in moments (with and without visual occlusion), significantily differences are observed, in which, they are higher for the group of athletes compared with the non-athletes group on the moment with visual occlusion in all the game situations. Furthermore, on the moment without occlusion more options were created then on the moment with occlusion in the two groups. Given the results found, we conclude that young volleyball athletes perform faster fixations in situations of AC and take more correct decisions in attacking situation (AE and AC) compared to non-athletes. The different strategies of visual search in moments with and without occlusion are perceived as un important factor that prove the differences found on the results of this study, affirming the hypothesis proposed by Johnson and Raab (2003), that the difference between the number and the types of generated options depends on the strategies used for the resolution of a certain action.